Antisite defect manipulation enables the high thermoelectric performance of p-type Bi2-xSbxTe3 alloys for solid-state refrigeration. (October 2022) - Li, Shan; Fang, Xingce; Lyu, Tu; Cheng, Jiahui; Ao, Weiqin; Zhang, Chaohua; Liu, Fusheng; Li, Junqin; Hu, Lipeng
Abstract: In thermoelectrics, carrier concentration, carrier mobility, density-of-state effective mass, and lattice thermal conductivity are all intimately associated with native point defects. Taking p -type Bi0.4 Sb1.6 Te3 polycrystal as an example, the excessive antisite defects results in too high carrier concentration and inferior carrier mobility. Herein the constructive role of antisite defect manipulation for enhancing thermoelectric performance of Bi0.4 Sb1.6 Te3 is reported. We explored the thermoelectric study of sole Gallium or Indium-doped p -type Bi0.4 Sb1.6 Te3 in two distinct compositional series: Bi0.4 Sb1.6- x Ga x Te3 and Bi0.4 Sb1.6- y In y Te3, aka the x -series and y -series. In x -series, the fine-tuning of antisite defects is achieved for the first time via the reciprocal variation of electronegativity difference and atomic size difference between cations and anions on the grounds of chemical composition-regulated ( χ, r ) model. Compared to the dramatic reduction of antisite defect concentration for y -series, the slightly declined antisite defect concentration for x -series contributes to a more optimized carrier concentration and superior material parameter. In addition, the generated multiscale microstructures induced by Ga doping and hot deformation substantially diminish the lattice thermal conductivity through broad wavelength phonon scattering. As a result, a state-of-the-art zT = 1.47 at 350 K is attained in p -type Bi0.4 Sb1.59 Ga0.01 Te3, indicating the potential advantages in solid-state refrigeration field. These results not only attest to the efficacy of native point defect engineering in V2 VI3 and other thermoelectric materials, but also bring out the understanding and manipulation of native point defect to a new level. Graphical abstract: Image 1 Highlights: The reciprocal variation of Δ χ and Δ r leads to the fine-tuning of antisite defects. Fine-tuning of antisite defect in Bi0.4 Sb1.6 Te3 is realized via Ga doping. Antisite defect manipulation optimizes carrier concentration and carrier mobility. Induced multiscale microstructures decrease lattice thermal conductivity. A state-of-the-art zT = 1.47 at 350 K is attained for p -type Bi0.4 Sb1.59 Ga0.01 Te3 .